Associations of neighborhood infrastructure with cardiovascular diseases and their risk factors: results of the ESSE-RF-3 epidemiological study - S. A. Maksimov; M. B. Kotova; S. A. Shalnova; Yu. A. Balanova; A. E. Imaeva; V. А. Kutsenko; S. E. Evstifeeva; A. V. Kapustina; G. A. Muromtseva; N. S. Karamnova; O. B. Shvabskaya; T. V. Repkina; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To analyze the association of neighborhood infrastructure with cardiovascular diseases (CVDs) and their risk factors (RFs) in a representative all-Russian adult population sample.Material and methods. Data from the ESSE-RF3 study conducted in 2020-2022 in 15 Russia regions were used. The total sample included 28731 men and women aged 35-74 years. The neighborhood infrastructure was assessed using the Russian version of the (Neighborhood Environmental Walkability Scale (NEWS). The following CVDs and their risk factors were assessed: hypertension, obesity, hypercholesterolemia, alcohol abuse, smoking, diabetes, coronary artery disease, myocardial infarction, stroke, and cancer. Associations of disease outcomes with neighborhood infrastructure were assessed using logistic regression with adjustment for individual sociodemographic characteristics.Results. Population density, distance from infrastructure facilities to home, accessibility of infrastructure facilities, walkability and aesthetics of the area, as well as safety related to traffic and crime, are associated with CVDs and their risk factors. The greatest number of associations are noted with smoking, alcohol abuse, obesity, diabetes and hypertension.Conclusion. The study results confirm the need to take into account the neighborhood infrastructure when assessing cardiovascular risk, implementing preventive strategies and urban planning decisions.